Simulating immunosuppressive mechanism of Microplitis bicoloratus bracovirus coordinately fights Spodoptera frugiperda - Li, Xing-Cheng; Ma, Yin-Chen; Long, Jin; Yan, Xiang; Peng, Nan-Nan; Cai, Cheng-Hui; Zhong, Wen-Feng; Huang, Yong-Biao; Qiao, Xin; Zhou, Li-Xiang; Cai, Qiu-Chen; Cheng, Chang-Xu; et al. (Frontiers in Immunology, 2023)
Parasitoid wasps control pests via a precise attack leading to the death of the pest. However, parasitoid larvae exhibit self-protection strategies against bracovirus-induced reactive oxygen species impairment. This has a detrimental effect on pest control. Here, we report a strategy for simulating Microplitis bicoloratus bracovirus using Mix-T dsRNA targeting 14 genes associated with transcription, translation, cell-cell communication, and humoral signaling pathways in the host, and from wasp extracellular superoxide dismutases. We implemented either one-time feeding to the younger instar larvae or spraying once on the corn leaves, to effectively control the invading pest Spodoptera frugiperda. This highlights the conserved principle of "biological pest control," as elucidated by the triple interaction of parasitoidbracovirus-host in a cooperation strategy of bracovirus against its pest host.